2021
DOI: 10.1089/chi.2021.0177
|View full text |Cite
|
Sign up to set email alerts
|

Design and Approach of the Healthy Weight Clinic Pediatric Weight Management Intervention Package and Implementation: Massachusetts-CORD 3.0

Abstract: Background: Although proven effective interventions for childhood obesity exist, there remains a substantial gap in the adoption of recommended practices by clinicians.Objective: The aims are to: (1) package implementation and training supports to facilitate the adoption of the evidence-based Healthy Weight Clinic Pediatric Weight Management Intervention (PWMI) (based on three previous effectiveness trials); (2) pilot and evaluate the packaged Healthy Weight Clinic PWMI; and (3) develop a sustainability and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
2
8
1
Order By: Relevance
“…The active intervention, referred to as family-based behavioral treatment , has been tested before in non–primary care settings and led to sustained improvements in both parent and child weight outcomes . The PLAN trial advances the field by embedding this previously tested obesity treatment intervention into pediatric primary care practices, which is in line with other recent attempts to improve the reach of pediatric weight management programs by situating them outside of specialty clinics . However, the average effect on child weight in this study was lower than what has been reported in previous trials of family-based behavioral treatment, falling below the threshold of a clinically meaningful weight change .…”
supporting
confidence: 51%
“…The active intervention, referred to as family-based behavioral treatment , has been tested before in non–primary care settings and led to sustained improvements in both parent and child weight outcomes . The PLAN trial advances the field by embedding this previously tested obesity treatment intervention into pediatric primary care practices, which is in line with other recent attempts to improve the reach of pediatric weight management programs by situating them outside of specialty clinics . However, the average effect on child weight in this study was lower than what has been reported in previous trials of family-based behavioral treatment, falling below the threshold of a clinically meaningful weight change .…”
supporting
confidence: 51%
“…Our findings from this study, informed our discussions in our technical assistance calls which occurred every 2 weeks throughout the intervention with implementing staff and our stakeholder meetings. In addition, the group curriculum, provider training, how to form clinic-community partnerships, how to create a sustainable model and addressing social determinants of health and barriers to retention and engagement have been integrated into our current HWC package that was created in collaboration with the American Academy of Pediatrics Institute for Childhood Healthy Weight and funded by the Centers for Disease Control for national dissemination ( 27 , 28 ). The program is now being implemented by eight health centers in Mississippi and Massachusetts.…”
Section: Discussionmentioning
confidence: 99%
“…This created a complete conceptual model of which strategies would be used to overcome barriers identi ed by stakeholders. (19) Moreover, including adaptations suggested by pre-implementation sites stakeholders could help create a sense of ownership of the intervention amongst staff in the Mississippi FQHC's and keep them engaged to continue to offer HWC to their communities past the study period. As HWC moves into dissemination stages, understanding these determinants as categorized using CFIR, and with associated evidence-based strategies to overcome barriers and leverage facilitators, can help facilitate adoption in new sites.…”
Section: Discussionmentioning
confidence: 99%
“…Additional details about HWC have been published. (19) The FQHCs implementing HWC are located in the Delta region of Mississippi. These FQHCs serve a large proportion of children from families with lower income and Black children.…”
Section: Participants and Settingsmentioning
confidence: 99%
See 1 more Smart Citation